Targeting the Trimolecular Complex: The Pathway Towards Type 1 Diabetes Prevention - Michels, Aaron W. (Mary Ann Liebert, Inc., 2013)
George Eisenbarth devoted his life to understanding the basic immunology of the autoimmune polyglandular syndromes and type 1 diabetes, while providing exceptional clinical care to individuals afflicted with these disorders. Over the last 5 years, I was privileged to know George Eisenbarth as a mentor, colleague, and friend. His enthusiasm for science and specifically understanding the basic immunology of type 1 diabetes was infectious. George was the first to initially hypothesize that type 1 diabetes is a chronic autoimmune disorder. He made diabetes a predictable disease by developing biochemical assays to measure islet autoantibodies and provided this technology worldwide to researchers and the medical community. His work identifying and detecting islet autoantibodies allowed for clinical intervention trials aimed at preventing type 1 diabetes. George worked fervently to prevent the disease. During my time as a fellow in George's laboratory and faculty member at the Barbara Davis Center for Diabetes, we focused our efforts for diabetes prevention at the trimolecular complex (human leukocyte antigen molecule, self-peptide, and T cell receptor), which plays a pivotal role in diabetes pathogenesis. It is our belief that targeting this complex with safe and specific therapies will lead to the prevention of type 1 diabetes and an improved understanding as to why diabetes develops.